Students' Perceptions of Safety on a Campus in Relation to Firearms - Gallegos, Porfirio (2018)
This study will utilize a qualitative approach to better understand students' perceptions of safety on-campus in relation to firearms. Results found that participants felt safe on-campus due to its rural setting. Determination of geographical upbringing was noted as influential overall in perceptions of firearms. Participants were more confident with faculty having concealed firearms than students. Results also indicated that students have a lack of knowledge when it came to state legislation, their university's policies, and the protocol in place at their university in response to a mass shooting. Students reflected Perry's (2010) multiplicity stage of development appropriate for this age group. Recommendations to the University Police Department, and University Housing and Dining were provided to gain insight into the challenges and developmental factors that face students who chose to live on campus